ARCHERY AND THE SUNNAH:A BUSINESS JOURNEY TO RESTORE THE PROPHETIC WAY OF LIFE - Wan Husain, Wan Rohaida (IIUM Journal of Case Studies in Management, 2025)
This case study explores how Excella Archery can strategically position itself as a leading business that promotes the Sunnah of Prophet Muhammad ? through the practice of archery, by leveraging the spiritual, educational, and cultural dimensions deeply rooted in Islamic heritage. By aligning its brand identity with the Prophet’s encouragement of archery, Excella Archery has the unique opportunity to differentiate itself in a competitive market through authentic faith-based engagement. The study outlines key strategies, including integrating Islamic teachings into training programmes, the development of culturally inspired products, community partnerships, and educational content creation. These initiatives nurture personal growth in discipline, focus, and spirituality and foster strong community bonds among Muslim consumers. Ultimately, this approach positions Excella Archery as a pioneer in combining business innovation with religious and cultural preservation, inspiring a new generation to embrace archery as a sport and a Sunnah.